PENGEMBANGAN SISTEM PEMANTAUAN HUJAN BERBASIS WEB - Candra Nur Ihsan (Universitas Widyatama, 2019)
The weather in Indonesia has an important influence on the activities that humans will carry out, both for individuals and groups. In the current technological era the application of a weather monitoring system needs to be carried out to provide anticipation to planned activities and also to the potential for existing disasters, especially during rainy weather. At the National Aeronautics and Space Agency (LAPAN) makes rain radar technology based on ship